Chronic treatment of (+)-methamphetamine-induced locomotor effects in rats using one or a combination of two high affinity anti-methamphetamine monoclonal antibodies. Issue 9 (1st September 2016) - Hambuchen, Michael D.; Rüedi-Bettschen, Daniela; Gunnell, Melinda G.; Hendrickson, Howard; Owens, S. Michael
ABSTRACT: We hypothesized that treatment of methamphetamine (METH) effects with a mixture of 2 high affinity anti-METH monoclonal antibodies (mAb) with differing molecular recognition for METH-like structures could increase efficacy compared to treatment with a single mAb. The antibodies studied were mAb7F9 (METH and amphetamine [AMP] KD = 7.7 and 270 nM) and mAb4G9 (16 nM and 110 nM, respectively) in a 50:50 mixture. Adult male Sprague Dawley Rats were treated with iv saline or a loading dose of mAb7F9-mAb4G9 (141 mg/kg of each mAb) followed by 2 weekly doses (70.5 mg/kg total) on days 7 and 14. METH challenge doses (0.56 mg/kg) were administered 4 hrs and 3 days after each mAb7F9-mAb4G9 treatment, and 7 days after the final treatment (day 21). Locomotor activity (0–4 hrs) and serum METH and AMP concentrations (at 5 hrs) were measured after each METH challenge. MAb7F9-mAb4G9 treatment significantly reduced the duration of locomotor activity after 6 of the 7 METH doses ( P < 0.05 ) and significantly increased serum METH and AMP concentrations. Administering three-fold higher METH doses (1.68 mg/kg) on days 24 and 28 showed mAb7F9-mAb4G9 treatment had negligible effects on the duration of METH-induced locomotor activity. These data were then compared to previous monotherapy data. While mAb7F9-mAb4G9 therapy inhibited the effects of multiple METH challenge doses, the inhibition was not as profound or as long lasting as the effects of mAb7F9 treatment alone. These data demonstrate the importance of both mAb affinity and specificity in the production of effective, long-lasting anti-METH mAb therapies.